Pengaruh Pemberian Kredit terhadap Laba pada PT Bank Tabungan Pensiunan Nasional Tbk. Kantor Cabang Bandar Lampung - Riki Renaldo; Diana Lestari (Universitas Mitra Indonesia, 2020)
Lending is the backbone of banking activities. And if we look at the bank's income side, we will find that the bank's biggest income is from income by giving credit. Lending will generate income, and income will increase profits. This study aims to determine how the influence of lending to earnings at PT Bank National Savings Pension Tbk Bandar Lampung Branch Office. In this study lending as an independent variable and profit as the dependent variable, and carried out for the period 2011 to 2013. The method used is descriptive analysis with a quantitative approach. The analysis used is quantitative and qualitative. Based on the analysis and discussion using SPSS, it is known that the magnitude of the effect of giving credit to earnings amounted to 95,896. Simultaneously lending has a significant effect on earnings at PT Bank Tabungan Pensiunan Nasional Tbk Bandar Lampung Branch Office. Furthermore, partially 95,896 is greater than 2.63, then credit extension has a significant effect on profits at PT Bank Tabungan Pensiunan Nasional Tbk Bandar Lampung Branch Office.